التفكير اللغوي عند يونس بن حبيب وأثرة في التقعيد اللغوي - شحادات، مجدي حسين أحمد (جامعة قاصدي مرباح ورقلة - كلية الآداب واللغات - مخبر التراث اللغوي والأدبي في الجنوب الشرقي الجزائري, 2023)
يتناول هذا البحث بالدراسة الأثر الفكري الذي تركه يونس بن حبيب في النشاط اللغوي عند العرب في فترة ما قبل التقعيد. إذ قامت الدراسة بداية على حصر اهتمامها بحياة يونس بن حبيب- الإنسان العالم- وشيوخه وتلاميذه؛ للوقف على سيرته لعلها تضيء بعض ما استغلق من آرائه وطبيعة أفكاره، ثم سعت الدراسة للكشف عن إسهاماته النحوية، بالاعتماد على مصدرنا اليتيم وهو كتاب سيبويه الذي أتاح لنا النظر في بعض آرائه ودراستها وتتبع أصولها. وعرضت الدراسة لأهم المناقشات بين يونس وسيبويه، فتارة وجدنهما يتفقان وتارة أخرى يختلفان، كما لاحظنا الشيء ذاته عند مقارنة آراء يونس وآراء الخليل بن أحمد الفراهيدي. وخلصت الدراسة في النهاية إلى أن يونس بن حبيب وأستاذه أبو عمرو بن العلاء قد شكلا تيارا مستقلا في النحو العربي يعتمد على السماع أكثر من القياس. This study deals with the intellectual impact that Yunus bin Habib presented on the linguistic activity of the Arabs in the period preceding the contracting phase, as the study was based from the beginning on limiting its interest in Yunus bin Habib, the human being. It examines his life, his elders, and his students to find out about his biography, perhaps illuminating for us some of his views and the nature of his ideas, and then the study sought to uncover his grammatical contributions, relying on our orphan source, a book that allowed us to consider some of his opinions, study them and trace their origins. The study presented the most important discussions between Yunus and Sibawayh. Sometimes they found them agreeing and at other times disagreeing. We also observed the same thing when comparing Yunus’s views and ALkaleel’s views. The study concluded in the end that Yunus bin Habib and his teacher Abu Amr bin Ala had formed an independent stream in Arabic grammar that relied more on hearing than analogy.
Keywords: الفكر اللغوي -- تاريخ النحو العربي -- منهج التقعيد -- المدارس النحوية -- أعلام علم النحو -- النحوي، يونس بن حبيب، ت. 182 هـ